Clinical Characteristics and Risk Factors of Recurrent Mooren’s Ulcer - Lixia Yang; Juan Xiao; Jiawei Wang; Han Zhang (Journal of Ophthalmology)
Purpose. To investigate the clinical characteristics of Mooren’s ulcer in East China and to identify the potential risk factors that affect the recurrence of Mooren’s ulcer. Methods. We reviewed the medical records of 95 patients (100 eyes) diagnosed with Mooren’s ulcer from May 2005 to December 2014. The patients were classified into recurrent and nonrecurrent groups and followed up for 18 months. The difference between two groups was estimated. The patients in the recurrent group were subdivided according to the history of corneal infection and corneal perforation, respectively. The recurrent time in the subgroups was analyzed. Results. Patients in the recurrent group were more likely to have a history of corneal infection and corneal perforation than that in the nonrecurrent groups. In patients with recurrent Mooren’s ulcer, the median time to first recurrence was 130 days in the infection group, 480 days in noninfection group, and 195 days in the perforation group versus 480 days in nonperforation group. Conclusion. Corneal infection and corneal perforation were associated with early recurrence of Mooren’s ulcer. The tailored follow-up schedule should be used for patients with corneal infection and corneal perforation due to the high risk of recurrence.